(untitled) (Student Conference Proceedings, 2025)
Walking in nature can have a positive impact on physical health and psychological well-being but the effect on cognitive functioning remains less clear. To further investigate this relationship, 50 university students were tested in a series of cognitive tasks before and after a 15-minute walk either across an urban university campus (urban group) or a nature trail (nature group). Both groups exhibited higher test scores in the attentional task (d2-R) after walking, while only the urban group showed better working memory (Digit Span task). Neither group demonstrated higher executive functioning (Trail Making Test). The results of this pilot study suggest that taking a short walk in nature can improve specific cognitive abilities, but the effects were not superior to an urban condition. This, in turn, opens up avenues for future research.